COMPARISON OF MYOCARDIAL BLUSH GRADE IN STEMI PATIENTS WITH AND WITHOUT RESOLUTION ON RECIPROCAL ST SEGMENT DEPRESSION UNDERGOING PRIMARY PERCUTANEOUS CORONARY INTERVENTION - M. Fahrial Siregar, Nizam Z. Akbar, Ali Nafiah Nasution, Harris Hasan, Zulfikri Mukhtar & Hilfan A.P. Lubis (International Journal of Research Science and Management, 2020)
Background: Acute coronay syndrome is one of the problems in cardiovascular system. The revascularization recommended according to the ESC Guidelines for the management of acute myocardial infarction in patients presenting with ST-segment elevation (STEMI) (2017) are Primary Percutaneous Coronary Intervention (Primary PCI). ST Segment Depression (STSD) in the tapping area in the opposite direction from the infacrtion area (non infarction area) of STEMI. Myocardial Blush Grade (MBG) to assess the effectiveness of myocardial reperfusion. This study aim to assess the differences of MBG with or without reciprocal STSD resolution in STEMI patients with <12 hour onset undergoing primary PCI strategy. Methods: This study is a cross sectional study, in which 67 STEMI patients with onset <12 hours who underwent primary PCI therapy strategies at H. Adam Malik General Hospital, Murni Teguh Memorial Hospital, and Grandmed Hospital starting October 2018. Results of Myocardial Blush Grade (MBG) after primary PCI and electrocardiography evaluation of STSD changes in reciprocal leads at the start from emergency department (before primary PCI) and 90 minutes after Primary PCI. Statistical analysis was perfomed to assess the difference between MBG with or without reciprocal STSD resolution in STEMI patients undergoing primary PCI. Results: From 67 patients, 35 patients had reciprocal STSD resolution with MBG 3, and 32 patients without reciprocal STSD resolution with MBG ≤2. From the basic criteria of this research subjects to MBG, there are significant difference in infarct location (p 0.001) and KILLIP classification (p<0.005). This study found significant difference between MBG and reciprocal STSD resolution (p<0.001). Conclusion: There is a significant difference between MBG with reciprocal STSD resolution compared without reciprocal STSD resolution after primary PCI.